Copper Tetra-Tert-Butyl Phthalocyanine Thin Films for Ammonia Gas Detection - Ameer A. Alhusseiny (Journal of Global Pharma Technology, 2020)
Thin films of copper tetra-tert- butyl Phthalocyanine (CuPc) have been prepared from their solution in chloroform using spin coating technique. Films then heated to (100, 200 and 300) oC to study the effect of annealing temperature on the characteristics of the prepared films. UV-visible spectrophotometer was used to investigate the absorption properties of the materials as well as the optical energy gaps. The morphology characteristics have been carried out utilizing atomic force microscopy (AFM). To demonstrate the sensing properties of CuPc films, I-V measurements were carried out using Keithly 2400 instrument to calculate the resistance before and after exposure to ammonia odorant. The prepared samples show a decrease in the resistance values after exposure to the contaminated air. Time dependency was also carried out to investigate the response and recovery time of the prepared device.Keywords: Copper phthalocyanine, Thin films, Gas sensor, Ammonia detection.